Transformation of East Java MSMEs: Superior Strategies for Independence and Sustainability (Proceeding of the International Conference on Economics, Accounting, and Taxation, 2025)
This research aims to formulate a strategy to enhance the competitiveness and sustainability of SMEs in East Java, supporting their independence. Using a descriptive qualitative method, data collection involved observation, interviews, and documentation. Key informants included SME actors, relevant agency officials, representatives from SME Banks in East Java, and academics. The analysis revealed that the strategy for enhancing competitiveness focuses on adopting digital marketing, product and process innovation, and strengthening partnerships with government, financial institutions, and large companies to expand market access and resources. Sustainability is supported by effective financial management, compliance with legal requirements, and potential circular economy practices for resource efficiency. The strategy for independence emphasizes entrepreneurship training, mentoring, easier access to capital, and facilitating business matching and exhibitions for market expansion. The government and supporting institutions play a vital role in creating a conducive ecosystem. The relationship between competitiveness, sustainability, and independence is synergistic: increasing competitiveness enhances sustainability, which in turn stabilizes the business environment. Independence allows SMEs to be proactive in achieving both competitiveness and sustainability. With sustained support, East Java's SMEs have significant growth potential, contributing to the economy, but policies, empowerment programs, and resource access facilitation will be crucial to realizing their full potential.